Exploring the Potential Genetic Heterogeneity in the Incidence of Hoof Disorders in Austrian Fleckvieh and Braunvieh Cattle - Kosińska-Selbi, Barbara; Suchocki, Tomasz; Egger-Danner, Christa; Schwarzenbacher, Hermann; Frąszczak, Magdalena; Szyda, Joanna (Frontiers in Genetics, 2020)
Genetic heterogeneity denotes the situation when different genetic architectures underlying diverse populations result in the same phenotype. In this study, we explore the genetic background underlying differences in the incidence of hoof disorders between Braunvieh and Fleckvieh cattle in the context of genetic heterogeneity between the breeds. Despite potentially higher power of testing due to twice as large sample size, none of the SNPs was significantly associated with the total number of hoof disorders in Fleckvieh, while 15 SNPs were significant in Braunvieh. The most promising candidate genes in Braunvieh were: CBLB on BTA1, which causes arthritis in rats; CAV2 on BTA4, which effects skeletal muscles in mice; PTHLH on BTA5, which causes disease phenotypes related to skeleton in humans, mice and zebrafish; SORCS2 on BTA6, which causes decreased susceptibility to injury in mice. Some of significant SNPs (BTA1, BTA4, BTA5, BTA13, BTA16) revealed allelic heterogeneity – i.e. different allele frequencies between Fleckvieh and Braunvieh. Some of the significant regions (BTA1, BTA5, BTA13, BTA16) correlated to inter-breed differences in linkage disequilibrium (LD) structure and may thus represent false-positive heterogeneity. However, positions on BTA6 (SORCS2), BTA14 and BTA24 mark Braunvieh-specific regions. We hypothesize that the observed genetic heterogeneity of hoof disorders is a by-product of different selection goals defined for the analysed breeds – towards dairy production in Braunvieh and towards beef production in Fleckvieh. Based on the current dataset it is not possible to unequivocally confirm or exclude the hypothesis of genetic heterogeneity in the susceptibility to hoof disorders between Fleckvieh and Braunvieh. The main reason for the problem is that the potential heterogeneity was explored through SNP-phenotype associations and not through causal mutations, due to a limited SNP density offered by the SNP-chip. The rationale against genetic heterogeneity comprise a limited power of detection of true associations as well as differences in the length of LD blocks and in linkage phase between breeds. On the other hand, different selection goals defined for the analysed breeds accompanied by no systematic, genome-wide differences in LD structure between the breeds favour the heterogeneity hypothesis at some smaller genomic regions.